PENGARUH LOKASI USAHA, EVENT KHUSUS, DAN PERILAKU KONSUMEN TERHADAP MINAT PELANGGAN PADA UMKM TOKO BUKET AMARANTA FLOWERS DI DESA PERGUNG, JEMBRANA - Berty Septya Ayu Devi; Putu Lidia Marini; Luh Gede Putri Kusuma Pekerti (Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of business location, special events, and consumer behavior on customer interest at Amaranta Flowers Bouquet Shop MSMEs in Pergung Village, Jembrana. The research employed a quantitative approach with an explanatory research design. Data were collected through observation, interviews, and questionnaires distributed to Amaranta Flowers customers using a saturated sampling technique. Data analysis was conducted using multiple linear regression, t-test, F-test, and coefficient of determination. The results indicate that business location, special events, and consumer behavior have a positive and significant partial effect on customer interest. Simultaneously, these three variables also have a positive and significant effect on customer interest. These findings suggest that a strategic location, attractive events, and positive consumer behavior are important factors in increasing customer interest in florist businesses.